Fiscal Consolidation Strategy: Phased vs. Direct, Which is Better? - Muhammad Rheza Ramadhan (Gorontalo State University, 2023)
This research aims to examine the impact of fiscal consolidation on the US economy. Since COVID-19 caused the government to cut expenditures due to higher health and business incentive expenditures, fiscal consolidation is required. The analysis is divided into three parts. First, we assume that the decrease in government expenditure is accomplished in the first year. Second, we suppose that government expenditure is progressively reduced, by 0.25% in the first year, 0.50% in the second year, 0.75% in the third year, and 1% in the fourth year. The last scenario predicts that the rest of the globe will follow fiscal consolidation. Following the investigation, we can conclude that fiscal consolidation has a significant long-term influence on the economy. Even while real GDP is declining in the near term, reductions in government expenditure may enhance real GDP in the long run. Based on the comparison of the first and second scenarios, we can conclude that gradual fiscal consolidation is preferable since real GDP does not fall immediately in the first year. Furthermore, we know that the impact of fiscal consolidation in the third scenario is not as favourable as in the first and second scenarios regarding real GDP. As a result, we may assume that the fiscal consolidation policy will be less successful if other nations follow it.